The Concept of Muslim Women's Clothing in Tafsir al-Munir and Its Relevance to the Protection of Women - Aninda Luqyana Maghfira; Faridah; Indri Astuti (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study aims to analyze the concept of Muslim women's clothing in Wahbah Az-Zuhaili's Tafsir al-Munir, as well as its relevance in contemporary life. Muslim women's clothing in Islam not only serves to cover the aurat, but also reflects religious identity and piety. The method used in this study is a qualitative approach with a literature review, analyzing Tafsir al-Munir and related Quranic verses on Muslim women's clothing. The results of the study show that Tafsir al-Munir emphasizes the importance of loose, non-transparent, and non-tight clothing to maintain modesty and honor for women, as well as to protect them from slander and sexual violence. This tafsir also combines the tafsir bi al-ra'yi and bi al-riwayah approaches to provide an applicable interpretation of modern challenges, including the influence of globalization and fashion trends. This study also shows that Muslim women face significant challenges in applying clothing that is in accordance with sharia, namely the influence of foreign cultures, global fashion, and social pressure. The concept of Muslim women's clothing in Tafsir al-Munir is highly relevant to the lives of modern Muslim women, emphasizing the importance of wearing clothing that complies with Islamic law to protect one's honor and maintain Islamic identity. This research contributes to offering a relevant contextual interpretive approach to address the objectification of women through the strengthening of identity and protection through Muslim women's dress ethics.